COMPARISON OF LAPAROSCOPIC AND OPEN METHOD OF TREATMENT AT PATHOLOGY OF THE VAGINAL PROCESS OF THE PERITONEUM - M. I. Kogan; V. V. Sizonov; A. G. Makarov (Вестник урологии, 2016)
Abstract. The article contains literature review is devoted to the problem of hydrocele, comparison of different methods of treatment of patients with this pathology, and evaluation of postoperative complications.